Autologous blood products: Usage and preparation protocols. Issue 4 (25th October 2022) - Palaiologou, Archontia; Keeling, Francis
Abstract: Focused clinical question: What are the appropriate preparation protocols for autologous blood products to support their clinical utilization? Summary: Autologous blood products provide a unique clinical benefit. Their popularity among the professions is growing. However, as this is a rapidly evolving field, multiple modalities are presented within the literature. Frequently there is no demonstrated superiority to previous iterations. This brief review attempts to offer a concise chronology on their evolution, preparation, and where possible, evidence to support their clinical utilization. Conclusions: The field of autologous blood products is expanding rapidly. These products appear to yield variable clinical benefits in specific indications. However, evidence supporting their universal application is scant, and the superiority of one formulation versus another is yet to be demonstrated.